(NkRITIKA I PUBLICISTIKA(B: [1841-1866] / s (N~ASTX (B7s - (NnEKRASOW(B, (NnIKOLAJ aLEKSEEWI^s ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1967)
(Nw SEDXMOJ TOM WO[LA KRITIKA I PUBLICISTIKA (B1841-1866 (NGG(B.s
rus
Keywords: (NpUBLICISTIKAs; (No^ERKI(B, (N\SSEs; (NkRITIKAs